Analysis of the long term effects of a company tax cut - Michael Kouparitsas; Dinar Prihardini; Alexander Beames (The Australian Government, The Treasury, 2016)
For a small open economy, such as Australia, its living standards (per capita income) are determined by the level of its terms of trade, labour productivity, labour force participation and population. Australia's terms of trade, labour force participation and population growth are expected to be flat or declining in the foreseeable future which implies any improvement in Australia's living standards must be driven by a higher level of labour productivity. This paper shows that a company income tax cut can do that, even after allowing for increases in other taxes or cutting government spending to recover lost revenue, by lowering the before tax cost of capital. This encourages investment, which in turn increases the capital stock and labour productivity. Analysis presented here also suggests the long-term benefits accrue to workers and households via permanently higher after-tax real wages and consumption.
Keywords: H21; H25; H30; E27; 330; optimal taxation; company tax; tax reform; policy simulation